Kebermaknaan Hidup pada Pasien Kanker - I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
This study aims to determine meaningfull life in cancer patients in hospitals Wangaya Denpasar 2015. Kind of this research used descriptive research,used cross sectional method. This research used purposive sampling technique. Subject of this research is cancer patient, sample this research amounted to 23 people. Research data shows the majority of the 23 respondents have a high level meaningfull of life as much as 14 respondents (60,9 %), 8 respondents (34,8 %) have a middle level meaningfull of life score and 1 respondents (4,3 %) have low level meaningfull life.